2021
DOI: 10.1002/pc.26231
|View full text |Cite
|
Sign up to set email alerts
|

Study on the ageing effect of alumina/epoxy composites modified by atmospheric plasma jet

Abstract: Alumina/epoxy resin (Al 2 O 3 /EP) composite material is widely used in the manufacture of insulators. However, the operation environment of long-term high-voltage direct current will destroy Al 2 O 3 /EP surface insulating performance. In this article, Al 2 O 3 /EP was modified by atmospheric pressure Ar and Ar/CF 4 plasma jet, and its aging effect was studied by investigating the physicochemical characteristics and the electrical performances of the sample 0 $ 100 days after modification. The experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…AFM revealed a peak on the surface after 30 s of irradiation with Ar/0.5% O 2 plasma and He/0.5% O 2 plasma, and the roughness increased to 3.8 nm and 2.4 nm, respectively. [9] According to the literature, Ar plasma etching is relatively uniform. [73][74][75] Changing the type of combined gas with argon can also change the surface's hydrophobic/hydrophilic properties.…”
Section: Gas Typementioning
confidence: 99%
See 1 more Smart Citation
“…AFM revealed a peak on the surface after 30 s of irradiation with Ar/0.5% O 2 plasma and He/0.5% O 2 plasma, and the roughness increased to 3.8 nm and 2.4 nm, respectively. [9] According to the literature, Ar plasma etching is relatively uniform. [73][74][75] Changing the type of combined gas with argon can also change the surface's hydrophobic/hydrophilic properties.…”
Section: Gas Typementioning
confidence: 99%
“…Many studies have shown that single‐gas plasma treatment can improve fiber surface properties effectively. Oxidation reactions and variability of recombination chemical bonds and molecular chains after high‐energy plasma treatment, [ 9 ] and surface modification can be caused by ions, electrons, and excited‐state/metastable particles in plasma. [ 10 ] Free radicals are introduced into the polymer surface to improve surface wettability and adhesion, as revealed in.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma fluorination changes the physical and chemical properties of the composites by forming rough morphology and a fluorinated layer. 11 However, the above studies often only consider the improvement of flashover voltage, which may not be sufficient to meet the complex climate and environmental challenges faced in actual conditions. The collaborative improvement of flashover and hydrophobic properties still lacks efficient and reliable schemes.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the surface activity of polymer, the plasma surface modification of polymer is mostly adopted because of its efficiency and repeatability. [ 12,13 ] So far, several studies have been carried out to investigate the influence of plasma treatment on the mechanical properties of adhesively bonded thermoplastics. Tušek et al [ 14 ] improved the wettability and bondability of polyamide 6 (PA 6) films through NH 3 plasma treatment.…”
Section: Introductionmentioning
confidence: 99%